2020
DOI: 10.3390/rs12010131
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Changes in the Moisture/Dryness of Water Cavity Surfaces in Imlili Sebkha in Southwestern Morocco by Using Machine Learning Classification in Google Earth Engine

Abstract: Imlili Sebkha is a stable and flat depression in southern Morocco that is more than 10 km long and almost 3 km wide. This region is mainly sandy, but its northern part holds permanent water pockets that contain fauna and flora despite their hypersaline water. Google Earth Engine (GEE) has revolutionized land monitoring analysis by allowing the use of satellite imagery and other datasets via cloud computing technology and server-side JavaScript programming. This work highlights the potential application of GEE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
(102 reference statements)
0
4
0
1
Order By: Relevance
“…They are home to specific species of vegetation and fish that can survive in salinated environments, but their drainage networks are often underground, making them hard to identify in RS imagery. An RF model was used in [166] to identify water cavities where sebkhas form in Morocco. Wetland inventory maps are increasingly being used to inform carbon pricing, ecosystem service values, and conservation/restoration decisions.…”
Section: Wetland Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…They are home to specific species of vegetation and fish that can survive in salinated environments, but their drainage networks are often underground, making them hard to identify in RS imagery. An RF model was used in [166] to identify water cavities where sebkhas form in Morocco. Wetland inventory maps are increasingly being used to inform carbon pricing, ecosystem service values, and conservation/restoration decisions.…”
Section: Wetland Mappingmentioning
confidence: 99%
“…(2) SAR + optical RS images for better model performance: In addition, many studies reported [17,57,68,72,74,165,166,182,212,214] or suggested in future work [46,56,107,215] that SAR combined with optical RS images would improve model performance. Three classification methods (SVM, RF, and decision fusion) were used in [52] for the pixel-wise classification for crop mapping.…”
Section: Feature Engineering and Feature Importancementioning
confidence: 99%
See 2 more Smart Citations
“…Ghorbani 2019] e de [Hakdaoui et al 2020] investigaram e avaliaram a complementaridade dos dados do Landsat, Sentinel-2 e do Sentinel-1 em um ambiente no deserto de Imlili Sebkha (Marrocos). Os autores destacam a potencial aplicação do GEE no processamento de grandes quantidades de dados de satélite para observação de cavidades de água salgada permanentes, úmidas/secas, espaciais-temporais, livres e de longo prazo, além do monitoramento de umidade de Imlili Sebkha.…”
Section: Os Trabalhos De [Shami Andunclassified